Стойкий оловянный солдатик: [сказки] / Х. К. Андерсен - Андерсен Ханс Кристиан (Читаем сами, 2016)
Экземпляры: 21 (20180627) / Инвентарный номер: 62716 / Цена: 62.00 / Сис.шифр: 84 (4) / Авт.знак: А 65 / ГРНТИ: 17.82.93 / ББК: 84 (4)